Ursodeoxycholic acid in neonatal sepsis-associated cholestasis - Rita Mey Rina; Hanifah Oswari; Pustika Amalia (Indonesian Pediatric Society, 2014)
Background Sepsis-associated cholestasis (SAC) is an intrahepatic cholestasis caused by inflammatory cytokines. Patients with this condition have poor prognoses. Antibiotics are the mainstay of therapy, however, other adjuvant therapies, such as ursodeoxycholic acid (UDCA), have not been well established.Objective To assess the effect ofUDCA for treatment ofneonatal sepsis-associated cholestasis.Methods We performed a randomized, double-blind, controlled trial in 3 7 neonates who were diagnosed with sepsis-associated cholestasis in the Neonatal Care Unit of Cipto Mangunkusumo Hospital. Subjects were divided into two groups, with 19 neonates randomly allocated to the intervention group (received UDCA at 30 tngikg/day divided into 3 doses for 7 days) and 18 neonates to the control group (received placebo) . After 7 days of treatment, we evaluated the subjects' liver function parameters and performed asurvival analysis.Results Liver function parameter improvements at day 7 were not significantly different between the UDCA group and the control group, including for mean decrease of total bilirubin (TB) levels [2.2 (SD 2.9) mg/dL vs 1.7 (SD 4.6) mg/dL; P=0.080), mean decrease of direct bilirubin (DB) levels [1.1 (SD 2.3) mg/dL vs 0.6 (SD 3.6) mg/dL; P=0.080), median indirect bilirubin (lB) levels [0.4 (range 0.1- 5.6) mg/dL vs 0.9 (range 0.1-4.1) mg/dL; P=0.358) , mean decrease of alanine aminotransferase (ALT) levels [0.5 (-80.0 -21.0) U/L vs -2.0 (ranged -167 .0 - 85.0) U/L; P= 0.730), median aspartate aminotransferase (AST) levels [ 43 .0 (range 14.0-297 .0) U/L vs 150.0 (range 24.0-840.0) U/L; P=0.081), and median gamma-glutamyl transpeptidase (GGf) levels [125.0 (48.0-481.0) U/L vs 235.0 (56.0-456.0) U/L; P=0.108)). Five neonates in control group died compared to two in the UDCA group (P=0.232). In addition, UDCA did not significantly lengthen the survival time (hazard ratio/HR 3.62; 95%CI 0.69 to 18.77) .Conclusion Ursodeoxycholic acid tends to improve total bilirubin, direct bilirubin, and AST levels in sepsis associated cholestasis .